2019
DOI: 10.1002/acn3.744
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptor‐4 299Gly allele is associated with Guillain‐Barré syndrome in Bangladesh

Abstract: Objective TLR4 plays an important role in the pathogenesis of Guillain‐Barré syndrome (GBS). The relationships between TLR4 polymorphisms and susceptibility to GBS are poorly understood. We investigated the frequency and assessed the association of two single nucleotide polymorphisms (SNPs) in the extracellular domain of TLR4 (Asp299Gly and Thr399Ile) with disease susceptibility and the clinical features of GBS in a Bangladeshi cohort. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…[5][6][7][8][9] However, in certain pathogens such as Hepatitis E virus, this association has not been established globally, as it was only reported in Netherlands and Bangladesh. 104 Therefore, immunogenicity of COVID-19 in the development of GBS should consider the variations between different populations, [105][106][107][108] as epidemiologic studies involving certain populations might introduce bias in reporting results.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] However, in certain pathogens such as Hepatitis E virus, this association has not been established globally, as it was only reported in Netherlands and Bangladesh. 104 Therefore, immunogenicity of COVID-19 in the development of GBS should consider the variations between different populations, [105][106][107][108] as epidemiologic studies involving certain populations might introduce bias in reporting results.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of TLR4 in GBS patients have been repeatedly reported [ 9 , 24 ]. TLR4 299Gly polymorphisms were associated with an increased susceptibility to GBS [ 25 , 26 ]. While GBS has been considered as a post-infectious neuropathy, a strong response to TLR4 stimulation has been suggested as a critical host condition for Campylobacter jejuni triggered GBS [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous studies reported increased expression of TLR4 in GBS patients [ 148 ]. Moreover, TLR4 299Gly polymorphisms were associated with an increased susceptibility to GBS [ 149 , 150 ]. All this observations provide evidence to support TLR4 as a useful drug target for treating GBS, but trials using this therapeutic strategy are not yet planned.…”
Section: Guillain-barré Syndromementioning
confidence: 99%